2009
DOI: 10.1097/wnr.0b013e328325a8f9
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor MRI of the corpus callosum and cognitive function in adults born preterm

Abstract: Very preterm birth (before 33 weeks gestation) is associated with the white matter damage, and a common sequel is reduced size and altered shape of the corpus callosum. We used diffusion tensor MRI to assess the corpus callosum in 63 very preterm and 45 term-born young adults. Indices of white matter microstructure [fractional anisotropy (FA) and mean diffusivity (MD)] were obtained for the genu, body and splenium. Very preterm females had higher MD in the genu than term-born females, indicating altered white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 22 publications
2
69
0
2
Order By: Relevance
“…In a quantitative study of VLBW adolescents, including DTI, 35 a lower fractional anisotropy was detected in posterior aspects of CC. These findings have, however, been challenged in a recent DTI study 36 that demonstrated a higher MD in the genu of the CC and a significant association between the MD and IQ in prematurely-born females at age 18 years. No changes were seen in the splenium in this study nor in any parts of male CCs.…”
Section: Discussionmentioning
confidence: 72%
“…In a quantitative study of VLBW adolescents, including DTI, 35 a lower fractional anisotropy was detected in posterior aspects of CC. These findings have, however, been challenged in a recent DTI study 36 that demonstrated a higher MD in the genu of the CC and a significant association between the MD and IQ in prematurely-born females at age 18 years. No changes were seen in the splenium in this study nor in any parts of male CCs.…”
Section: Discussionmentioning
confidence: 72%
“…This finding matches the association reported between increased mean diffusivity in the splenium of the corpus callosum with a low performance intelligence quotient in adults born preterm. 22 Notably, we also observed decreased FA in the association fibers of the superior longitudinal fasciculus in children having decreased performance on any of the 3 subscales, suggesting that abnormalities in these regions presage subsequent global developmental impairment.…”
Section: Discussionmentioning
confidence: 72%
“…Widespread differences in white matter development have been frequently described in very preterm children throughout childhood and adolescence (14)(15)(16)(17). In general, white matter development comprises a cascade of events including the development of preoligodendrocytes, axons, and subplate neurons, which may be negatively affected in preterm children by multiple factors with accompanying excitotoxicity and ischemic events (18).…”
Section: Discussionmentioning
confidence: 99%